Intelligent Detector of Internal Combustion Engine Cylinder Pressure and Sensitivity Temperature Coefficient Compensation - Beirong Zheng; Chen Zhou; Xiaomin Pan; Quan Wang; Wei Xue (Advances in Materials Science and Engineering)
The detecting device based on mechanical mechanism is far from the measurement of internal combustion engine cylinder explosion and compression pressure. This pressure detection is under the environment of pulsed gas (over 500 times per one minute) and mechanical impactive vibration. Piezoresistive detection with silicon on insulator (SOI) strain gauges to pressure seems to be a good solution to meet such special applications. In this work, separation by implanted oxygen (SIMOX) wafer was used to fabricate the high temperature pressure sensor chip. For high accuracy and wide temperature range application, this paper also presents a novel pressure sensitivity temperature coefficient (TCS) compensation method, using integrated constant current network. A quantitative compensation formula is introduced in mathematics. During experiments, the absolute value of the compensated TCS is easy to be 10 × 10−6/°C~100 × 10−6/°C by individual adjustment and calibration of each device’s temperature compensation. Therefore, the feasibility and practicability of this technology are tested. Again, the disadvantages are discussed after the research of the experiment data and the improvement methods are also given in the designing period. This technology exhibits the great potential practical value of internal combustion engine cylinder pressure with volume manufacturing.